КЎҲНА УРГАНЧ – ШАРҚ МАДАНИЯТИ МАРКАЗЛАРИДАН БИРИ - Турганов, Б.К. (SCIENCE and SOCIETY, 2016)
The article deals with learning Kuhna-Urgench, one of the ancient cities of Central Asia, on the basis of written and archaeological resources. In the article it is mentioned that Kuhna-Urgench was a great cultural center of not only in Central Asia, but in the East too. At that period there were developed such spheres of economic and cultural relations as architecture, handicraft, trade, education and science.